(3GdChai aj TQM CSeGA Gddg GdMSfis - (3GdUhajhj GdMfaj, CHh HcQ Hf Ydjs
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdehUha HGdUaGJ GdYdjG hGdeYQha HGdCSeGA GdMSfi hGdUdGI Ydi QShdg GdCYdi hYdi Bdg GdCSfi (B( (3cPG (B) (3hHYO agPG eNJUQ eSei HGdChai aj TQM GdCSeGA GdMSfi hGdJj GTJedJ YdjgG QhGjI CHj gQjQI QVj Gddg Yfg Ydi eG fbdg GdEeGe GdSjhWj QMeg Gddg aj GdLGeY GdUZjQs
(3BNQgG (B:s
(3hbO bGd HYVge (B: (3Ef ddg JYGdi Cda GSe aCSeGA Gddg JYGdi EPf ZjQ efMUQI aj GdJSYI hGdJYSjf Hd CQGO HjGf Mce GdJSYI hGdJSYjf eY JQc GdJYQV dZjQgG Ch MUQ GdCSeGA GdehUhaI HUaI ef CMUGgG ONd GdLfI hbO GfJgi GdcdGe aj TQM CSeGA QH GdCfGe hGdMeO ddg Ydi GdJeGes
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds